Pengembangan Media Pembelajaran Digital berbasis Quizwhizzer pada Pembelajaran Sejarah Kelas XI SMA Negeri 13 Semarang Tahun 2026 - Adila, Amalia Syifana Nur; Romadi, Romadi (Jurnal Simki Pedagogia, 2026)
This study aims to analyze student needs, develop media, and test its feasibility in supporting student activity. The background of this study is the variety of media in history learning that has not been optimally integrated. This type of research is R&D (Research and Development) research using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques were carried out through interviews, conducting media validity tests, materials, and distributing response questionnaires. The results of the average media validity were 91.67% with the category "Very Valid". The average material validity was 100% with the category "Very Valid". Based on the results of the questionnaire, class XI students of SMA Negeri 13 Semarang obtained a percentage of 89% so it was declared "Very Practical". The results of the history teacher questionnaire obtained a percentage of 92% with the category "Very Practical". It can be concluded that Quizwhizzer-based learning media in history learning is declared very valid and practical to be used as an interactive learning medium.